OPTIMALISASI PERAN BADAN AMIL ZAKAT NASIONAL UNTUK KESEJAHTERAAN KOTA BATAM - RISKI, RISKI TRI PRASETYO JUNIOR; Lubna, Lubna Salsabila (LPPM Universitas Putera Batam, 2023)
The objective of this study is to examine the initiatives undertaken by the National Amil Zakat Agency for Batam City in their charitable endeavors pertaining to economic welfare businesses. This research aims to address the pressing issue of high poverty rates in Batam City and identify strategies to mitigate and overcome the factors that hinder progress in this area. Factors Affecting the Allocation of Zakat Funds to Enhance the Wellbeing of the Residents of Batam City. The primary objective of this study is to examine Law no. 23 of 2011, which pertains to the effective administration of Zakat funds. Specifically, the study aims to analyze the Collection, Management, and Distribution Scheme outlined in the aforementioned law. The present study employs field research methods utilizing a qualitative approach, specifically focusing on descriptive research. The primary objective of the author's research methodology is to carefully consider the processes and constraints that were present during the study, subsequently providing a comprehensive account of the empirical evidence and a coherent elucidation of the prevailing circumstances. The accuracy of the information gathered regarding the subject matter of the research is the determining factor. Based on the findings of this study, it can be inferred that the Batam City National Amil Zakat Agency has effectively facilitated the allocation of zakat funds to enhance the well-being of the local population in Batam City. However, the agency's ability to fully exploit its potential has been hindered by several constraints, notably limited resources. The accomplishments of the Batam city Baznas work program have demonstrated a significant impact on various aspects, including economic advancement and equitable allocation of resources among the underprivileged population in Batam city. Keywords: The Role of the Batam City Baznas, Management of Zakat, Welfare of the Community.